Frequency and magnetic field mapping of magnetoelastic spin pumping in high overtone bulk acoustic wave resonator - N. I. Polzikova; S. G. Alekseev; I. I. Pyataikin; V. A. Luzanov; A. O. Raevskiy; V. A. Kotov (AIP Advances, 2018)
We report on the first observation of microvolt-scale inverse spin Hall effect (ISHE) dc voltage driven by an acoustic spin pumping (ASP) in a bulk acoustic wave (BAW) resonator formed by a Al-ZnO-Al-YIG(1)-GGG-YIG(2)-Pt structure. When 2 mW power is applied to an Al-ZnO-Al transducer, the voltage VISHE ∼ 4 μV in the Pt film is observed as a result of resonant ASP from YIG(2) to Pt in the area ∼ 170 μm. The results of frequency and magnetic field mapping of VISHE(f,H) together with reflectivity of the resonator show an obvious agreement between the positions of the voltage maxima and BAW resonance frequencies fn(H) on the (f, H) plane. At the same time a significant asymmetry of the VISHE(fn(H)) value in reference to the magnetoelastic resonance (MER) line fMER(H) position is revealed, which is explained by asymmetry of the magnetoelastic waves dispersion law.